2005
DOI: 10.1115/1.1843851
|View full text |Cite
|
Sign up to set email alerts
|

Contact Analyses for Bodies With Frictional Heating and Plastic Behavior

Abstract: The stress field within machine components is an important indicator for contact failures. Since both thermal stresses due to frictional heating and plasticity are significant in engineering application, it is critical to predict the total stress field. In this work, the steady-state thermal effect is considered and a thermo-elastic–plastic contact model is developed. The model is applicable for rolling and/or sliding contact problem, as far as small equivalent plastic strain hypothesis is respected. Influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…The solver has since been developed and improved in several ways. Boucly et al [32] and Chen et al [33] introduced thermal aspects. Fulleringer and Nelias [34] focused on the influence of a cuboid of uniform plastic strain in a half space, on the normal and tangential displacements of surface points, and derived the corresponding Green's functions in an analytical form.…”
Section: Introductionmentioning
confidence: 99%
“…The solver has since been developed and improved in several ways. Boucly et al [32] and Chen et al [33] introduced thermal aspects. Fulleringer and Nelias [34] focused on the influence of a cuboid of uniform plastic strain in a half space, on the normal and tangential displacements of surface points, and derived the corresponding Green's functions in an analytical form.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the conjugate gradient method (CGM) [29,30] and the discrete convolution and fast Fourier transform technique [31] were utilized to reduce the computing time for solving contact problems. By using CGM and DC-FFT techniques, Boucly et al [32] studied contact analyses for bodies with frictional heating and plastic behavior, Wang et al [33] investigated the partial slip contact problem on three-dimensional layered materials, and Chen et al [34] studied the elasto-plastic indentation on layered materials using the equivalent inclusion method and given the yielding and plastic zone expansion behavior. On the other hand, Diao et al [35][36][37][38] proposed the two-dimensional (2D) local yield map for the indentation and friction of a coating-substrate system under sliding contact, whose study showed clearly that the ratio of the yield strength of the coating to the substrate, the ratio of the coating thickness to the Hertzian contact radius, and the friction coefficient play an important role in controlling the position of yielding.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal elasto-perfectly plastic contact model by Yu et al [12] considered the variation of the yield strength as a function of temperature. Recently, Boucly et al [13,14] developed a semi-analytical thermoelastic-plastic model to simulate the rolling/sliding contact between two smooth and two rough surfaces. A deterministic FEM two-dimensional steady-state thermal elasto-plastic asperity contact model is presented, in which the thermal expansion and thermal stress fields are fully coupled with the elasto-plastic behaviour of the material by using the FEM, initial stiffness method, and the incremental mathematical programming technique.…”
Section: Introductionmentioning
confidence: 99%